2008
DOI: 10.2478/v10045-008-0044-3
|View full text |Cite
|
Sign up to set email alerts
|

Management of Collar Rot of Chickpea (Cicer Arietinum) by Trichoderma Harzianum and Plant Growth Promoting Rhizobacteria

Abstract: Collar rot (Sclerotium rolfsii) of chickpea (Cicer arietinum) is one of the devastating soil-borne diseases of fungal origin, due to which 10-30% yield loss is recorded annually according to severity of the disease. Management of collar rot of chickpea is not feasible in the absence of effective soil fungicides. However, Trichoderma harzianum and plant growth promoting rhizobacteria (PGPR) have shown high efficacy against this disease in vitro as well as in the field. We used T. harzianum (10 4 , 10 6 and 10 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 18 publications
1
5
0
1
Order By: Relevance
“…Sclerotia were small, round and appeared like mustard seed. Similar results were reported by Maurya et al [18] , in chickpea. Observations on interaction effect of solvents, flowers and concentrations on dry mycelial weight of S. rolfsii were recorded and percent inhibition were determined and presented in Table 1.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Sclerotia were small, round and appeared like mustard seed. Similar results were reported by Maurya et al [18] , in chickpea. Observations on interaction effect of solvents, flowers and concentrations on dry mycelial weight of S. rolfsii were recorded and percent inhibition were determined and presented in Table 1.…”
Section: Resultssupporting
confidence: 92%
“…These results clearly indicate that biocontrol agents in combination with marigold flower extract provided protection to chickpea against collar rot. Maurya et al [18] reported 30-40% reduction in collar rot of chickpea with foliar application of T. harzianum and P. fluorescens.…”
Section: Effect Of Seed Treatment With Marigold Water Extractmentioning
confidence: 99%
“…Other recent studies also showed that different isolates of Trichoderma spp. had the ability to reduce the severity of foliar and root diseases (Muthukathan et al 2020), presumably by inducing systemic resistance in plants (Maurya et al 2008).…”
Section: Resultsmentioning
confidence: 99%
“…rolfsii Sacc. has been reported as the causal organism of dampingoff, root-,stem-, pod-rots and reduce of fresh and dry weight of Solanaceous plants (Okereke and Wokocha, 2007;Abiaa and Muhammed, 2008 ;Jin-hyeuk et al, 2008 andMaurya et al,2008).…”
Section: Introductionmentioning
confidence: 99%
“…Chemical control of damping -off and root rot of Solanaceous plants was also investigated by some researchers (Attia and Abada, 1994;Abd El-Kareem et al, 2004;Yaqub and Saleem, 2005;EL-Mohamedy et al, 2006;Palaiah et al,2007 andMaurya et al, 2008).…”
Section: Introductionmentioning
confidence: 99%